Reviews of D2D technology for 5G communication networks - Zhi-hong QIAN; Xue WANG (Tongxin xuebao)
On the basis of exploring D2D's leading role to developing trend of communication technologies in the future, some issues in terms of D2D system design are illustrated, like D2D device discovery, resource allocation, caching tech-nology and D2D-MIMO. Thereupon, the outline of separate data/control flattening 5G framework based on D2D is drawn, on the basis of optical fiber fronthaul and software defined network techniques. The mechanism, the lower macro/small base stations for access whereas the upper network cloud for management, is proposed. What emerges is that still major issues shall be faced by the research community, as D2D, SDN, edge computing and IOT technologies are expected to be introduced into the future mobile communication networks. The most relevant techniques for the future large-scale net-works, such as mobility, QoS and big data behavior, are addressed in details.